History of the Australian Vegetation: Cretaceous to Recent - S. Hill, Robert (University of Adelaide Press, 2017)
"The Australian vegetation is the end result of a remarkable history of climate change, latitudinal change, continental isolation, soil evolution, interaction with an evolving fauna, fire and most recently human impact. This book presents a detailed synopsis of the critical events that led to the evolution of the unique Australian flora and the wide variety of vegetational types contained within it. The first part of the book details the past continental relationships of Australia, its palaeoclimate, fauna and the evolution of its landforms since the rise to dominance of the angiosperms at the beginning of the Cretaceous period. A detailed summary of the palaeobotanical record is then presented. The palynological record gives an overview of the vegetation and the distribution of important taxa within it, while the complementary macrofossil record is used to trace the evolution of critical taxa. This book will interest graduate students and researchers interested in the evolution of the flora of this fascinating continent."